2010
DOI: 10.1177/0363546510361234
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Comparisons of Knee Stability After Anterior Cruciate Ligament Reconstruction Between 2 Clinically Available Transtibial Procedures

Abstract: Background: Several trials have compared the clinical results between anatomic double-bundle and single-bundle anterior cruciate ligament reconstruction procedures. However, it remains controversial whether the anatomic double-bundle procedure is superior to the single-bundle procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
120
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(122 citation statements)
references
References 42 publications
1
120
1
Order By: Relevance
“…However, recent studies suggesting the need for better rotational control have stimulated interest in a more anatomic reconstruction with double-bundle [6,9,21,26,38,41,49,51]. Several studies suggest the anatomic double-bundle ACLR should improve pivot shift resistance and increase rotational knee control [8,38,46,47,49,51] and should help preserve menisci and limit progression toward arthritis [8,38,46,47,49,51].…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies suggesting the need for better rotational control have stimulated interest in a more anatomic reconstruction with double-bundle [6,9,21,26,38,41,49,51]. Several studies suggest the anatomic double-bundle ACLR should improve pivot shift resistance and increase rotational knee control [8,38,46,47,49,51] and should help preserve menisci and limit progression toward arthritis [8,38,46,47,49,51].…”
Section: Introductionmentioning
confidence: 99%
“…Kanamori et al (2000) showed that anterior translation in the ACLdeficient knee resulting from a 10N·m internal rotation torque increased when that torque was combined with a 10N·m valgus torque; also ACL forces were greater with the combined torque. The most consistent finding in the ACL-deficient knee is an increase in anterior translation, where internal rotation was either not measured (Herbort et al, 2010;Yagi et al, 2002;Zantop et al, 2007), was found to be unchanged (Diermann et al, 2009;Seon et al, 2010) or increased (Kondo et al, 2010;Yamamoto et al, 2004). Studies have also sought to uncover the role of the ACL bands on combined internal rotation/valgus torque.…”
Section: Combined Internal Rotation/valgus Rotation -The 'Pivot Shift'mentioning
confidence: 92%
“…Single and double bundle reconstructions were both unable to reduce anterior translation on combined internal rotation/valgus torque (5N·m/10N·m), but the double bundle method reduced it more. Kondo et al (2010) performed a similar study. Both reconstructions showed significant decreases from deficient values in anterior translation on 90N anterior force, with the double bundle method showing significantly less translation, and values were not compared with the intact state.…”
Section: Effect Of Femoral Tunnel Sitementioning
confidence: 97%
“…Currently, double-bundle ACL reconstruction has been stated to provide a better rotational control and functional recovery than the single-bundle method (2)(3)(4). However, in many studies in which long-term follow-ups have been reported, no difference between the two methods has been observed in terms of anteroposterior stability, rotational stability, or functional results (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%